2009
DOI: 10.1175/2008jas2677.1
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Stochastic Kinetic Energy Backscatter Scheme and Its Impact on Flow-Dependent Predictability in the ECMWF Ensemble Prediction System

Abstract: Understanding model error in state-of-the-art numerical weather prediction models and representing its impact on flow-dependent predictability remains a complex and mostly unsolved problem. Here, a spectral stochastic kinetic energy backscatter scheme is used to simulate upscale-propagating errors caused by unresolved subgrid-scale processes. For this purpose, stochastic streamfunction perturbations are generated by autoregressive processes in spectral space and injected into regions where numerical integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
269
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(278 citation statements)
references
References 42 publications
3
269
0
6
Order By: Relevance
“…Two stochastic tendency perturbation schemes aim to mimic model errors. These are the stochastic kinetic energy backscatter scheme (Berner et al, 2009) and the stochastically perturbed parametrization tendency scheme Palmer et al, 2009).…”
Section: Copyright C 2012 Royal Meteorological Societymentioning
confidence: 99%
“…Two stochastic tendency perturbation schemes aim to mimic model errors. These are the stochastic kinetic energy backscatter scheme (Berner et al, 2009) and the stochastically perturbed parametrization tendency scheme Palmer et al, 2009).…”
Section: Copyright C 2012 Royal Meteorological Societymentioning
confidence: 99%
“…In previous work on stochastic parameterizations, both with the Lorenz '96 system (Wilks, 2005) and in other settings Neelin, 2000, 2003;Berner et al, 2009), it has been found that serially independent random numbers are relatively ineffective at improving ensemble forecast performance, and that serially dependent (i.e. temporally coherent) random innovations yield better forecast ensembles.…”
Section: Regression Emulatorsmentioning
confidence: 99%
“…The first introduction of stochastic parameterization into a realistic forecast model was described in the pioneering paper of Buizza et al (1999). Since that time stochastic parameterizations have been employed in operational settings, using weather-forecast and climate models from the European Centre for Medium-Range Weather Forecasts (Shutts, 2005;Berner et al, 2009Berner et al, , 2010, the UK Met Office (Bowler et al, 2009;Tennant et al, 2011), the Canadian Meteorological Centre (Charron et al, 2010) and in the USA (Hou et al, 2008;Teixeira and Reynolds, 2008). Stochastic parameterizations have in addition been used in research settings employing geographically explicit atmospheric models, in connection with the study of convection Neelin, 2000, 2003;Song et al, 2007), stratospheric dynamics (Piani et al, 2004) and tropical cyclone simulation (Snyder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are complemented by perturbations based on initial-time singular vectors (Buizza et al, 2008;Isaksen et al, 2010). Uncertainty of the forecast model formulation is represented in these experiments by stochastically perturbing the tendencies generated by the parameterization schemes (Buizza et al, 1999;Palmer et al, 2009) and by a stochastic kinetic energy backscatter scheme that adds a stream function forcing to the momentum equation (Berner et al, 2009). …”
Section: The Ensemble Prediction Systemmentioning
confidence: 99%